Influence of superheating on casting of gamma-TiAl - Barbosa, J. (2007)
In this work, a Tie48Al alloy was induction melted and allowed to cool and solidify in a ZrO2 based crucible with an inner layer of Y2O3, and the effect of superheating parameters (time and temperature) on the metalecrucible interface, alloy chemical composition, microstructure and microhardness is evaluated. Microhardness variation and segregation profiles of residual elements, namely yttrium and oxygen, from the surface to the inside of samples are presented and compared, in order to establish a relationship between the processing parameters, alloy contamination and the ‘‘alpha-case’’ extent. The alloy microstructure at the metalecrucible interface is characterized for each superheating time and temperature. The Y2O3 crucible layer was found to suffer some erosion and be slightly dissolved by the molten alloy and the extent of that dissolution, and consequent metal contamination with yttrium and oxygen, depend on both superheating temperature and holding time. A relationship was found between oxygen concentration profiles and microhardness profiles of the a2 þ g microconstituent, from the surface to the inside of samples, which depends on the superheating temperature, but is not affected by the holding time.